THE MEDIATING ROLE OF PRODUCT INNOVATION ON THE RELATIONSHIP BETWEEN MARKETING INFORMATION SYSTEM AND CUSTOMER ORIENTATION - Sabri ALWATTAR, Osamah Sohaib Mohammad; YURDAKUL, Melek (Journal of Economics and Administrative Sciences, 2021)
Marketing information system (KMIS) is an essential factor of developing business’ performance and getting sustainable success. The main goal of the research is to measure effect of MIS on customer orientation and product innovation. Also, another goal is to analyze the mediation role of product innovation in relationship MIS and customer orientation. This study sought to analyze the marketing information system and measure its effect on the customer orientation and product innovation. The data of the study were collected using questionnaire. The data were analyzed using statistical tools and SPSS programming. The results of the study showed that the KMIS can positively and significantly effect product innovation. Also, the results show that KMIS can positively and significantly effect customer orientation. Moreover, MIS and product innovation together can positively and significantly effect customer orientation. According to that, product innovation has a mediation role in relationship between KMIS and the customer orientation. The findings are important in terms of developing and revealing the effects of KMIS in Iraqi operations